ANALISIS FAKTOR YANG BERPENGARUH TERHADAP MORTALITAS PASIEN INTENSIVE CARE UNIT (ICU) DI RSUD Dr. SOEDIRMAN KEBUMEN - Diah Ayu Putriyanti; Kristin, Erna; Ratmasari, Dewi (Departemen of Health Policy and Management, Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2025)
Background: The ICU patient mortality rate is an indicator of hospital service quality. The ICU mortality rate at Dr. Soedirman Kebumen Regional General Hospital over the last five years has been over 40%. This rate is higher compared to the national ICU patient mortality rate in Indonesia, which is 27.6%. Objective: To identify factors influencing ICU patient mortality and to develop recommendations for an ICU mortality reduction program at Dr. Soedirman Kebumen Regional General Hospital. Methods: This study employed a mixed-methods research design with a sequential explanatory approach. Quantitative data were obtained from the medical records of ICU patients from July 2024 to December 2024. Qualitative data were gathered through in-depth interviews (management group) and focus group discussions (doctors and nurses). Quantitative data were analyzed using chi-square and Fisher's exact tests, as well as multivariate logistic regression. Qualitative data were analyzed using thematic analysis. Results: The study included 278 subjects, of whom 126 (45.3%) died in the ICU. Factors identified as significantly influencing ICU patient mortality at Dr. Soedirman Kebumen Regional General Hospital were age (p-value = 0.001), type of diagnosis (p-value = 0.008), Glasgow Coma Scale (GCS) score (p-value <0.001), use of mechanical ventilation (p-value <0.001), and length of stay (p-value = 0.004). The use of mechanical ventilation was the variable with the most significant influence on ICU patient mortality (p = 0.001, OR 43.73, 95% CI 15.84-120.72). Qualitative results suggested several programs to reduce ICU patient mortality, including: re-socialization of ICU admission criteria, activation of palliative care, improvement of human resources competency, multidisciplinary team collaboration, periodic evaluation of Early Warning System (EWS) implementation, evaluation of culture examination procedures, and initiation of High Care Unit (HCU) establishment. Conclusion: Age, type of diagnosis, Glasgow Coma Scale (GCS) score, use of mechanical ventilation and length of stay are factors influencing ICU patient mortality at Dr. Soedirman Kebumen Regional General Hospital. Given these factors contributing to the high ICU mortality rate, it is crucial for the hospital management to enhance service quality by implementing strategies to reduce ICU patient mortality at Dr. Soedirman Kebumen Regional General Hospital. Keywords: Intensive Care Unit, ICU, ICU mortality, determinants of ICU mortality, mortality reduction